Does trade among ASEAN members promote efficiency? sectoral evidence from the gravity model - Mohd Amin, Ruzita; Hamid, Zarinah; Md Saad, Norma (Centre for Promoting Ideas, USA, 2011)
This study investigates whether intra-ASEAN trade represents higher trade with efficient members (trade creating) or with inefficient members (trade diverting). Since ASEAN integration efforts are geared toward “open regionalism”, factors affecting both inter-industry and intra-industry trade at the disaggregated level are also identified. Using the extended gravity model, intra-ASEAN trade with efficient members is found for total exports, mainly contributed by five sectors: beverages & tobacco, minerals & fuels, chemicals & materials, machinery & transport equipment, and miscellaneous manufactures. Thus, this study finds that only „good‟, i.e., efficient intra-regional trade is taking place within ASEAN, which is in line with the objective of establishing the ASEAN Economic Community. Income levels, transportation costs as well as level of development are shown to have a significant effect on total trade as well as on most sectors. Based on the findings, the study provides policy recommendations to promote higher trade for ASEAN members.